2011
DOI: 10.1530/eje-10-1075
|View full text |Cite
|
Sign up to set email alerts
|

Bone loss after childhood acute lymphoblastic leukaemia: an observational study with and without GH therapy

Abstract: Objective: Bone mineral density (BMD) in survivors of acute lymphoblastic leukaemia (ALL) seems to vary with time, type of treatments and GH status. We aimed to evaluate BMD in ALL patients with GH deficiency (GHD), with and without GH therapy. Design: Case-control study. Methods: We examined 44 (21 women) GHD patients (median 25 years) treated with cranial radiotherapy (18-24 Gy) and chemotherapy and matched population controls for BMD with dualenergy X-ray absorptiometry. For 5 and 8 years, two subgroups wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…Therapy with methotrexate and particularly with corticosteroids is one of the most important factors which can interfere with bone metabolism. Other factors include irradiation and other hormonal deficiencies, especially of Growth Hormone (GH) and gonadotropins [11,21,[39][40][41][42].…”
Section: Causes Of Low Bone Mineral Density Among Acute Lymphoblasticmentioning
confidence: 99%
See 3 more Smart Citations
“…Therapy with methotrexate and particularly with corticosteroids is one of the most important factors which can interfere with bone metabolism. Other factors include irradiation and other hormonal deficiencies, especially of Growth Hormone (GH) and gonadotropins [11,21,[39][40][41][42].…”
Section: Causes Of Low Bone Mineral Density Among Acute Lymphoblasticmentioning
confidence: 99%
“…Cranial radiation therapy (CRT) at or above 24 Gy, craniospinal irradiation and total body irradiation (TBI) are some of the primary predictors of suboptimal BMD in ALL survivors [11,[39][40][41]. Low lumbar spine BMD was also associated with male or female gender, white race, lower BMI, and cumulative doses of glucocorticoid of at or above 5,000 mg [41,42].…”
Section: Causes Of Low Bone Mineral Density Among Acute Lymphoblasticmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that among adult ALL survivors, hormonal deficiencies, hypogonadism, insulin resistance, and dyslipidemia are prevalent (3,4,5,6). Low bone mineral density (BMD) and osteoporosis are also recognized complications of ALL, and according to some studies, adverse skeletal effects may persist until adulthood (7,8,9,10,11,12).…”
Section: Introductionmentioning
confidence: 99%